PATRIARKHISME DAN KETIDAKADILAN GENDER - Siti Rokhimah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This study discusses about what and how the patriarchal system perpetuates gender inequality in the reality of social life, with women as victims. Patriarchy is the magic system because of its ability to power that is no longer in the realm of the family but in all areas of the world that demonstrate extraordinary cognitive. This system is a system of male dominance and superiority -laki for control and domination of women. Gender roles are deliberately constructed by this ideology, understood by women as something natural or nature, so that in many areas of life this system perpetuates gender inequality.